2017
DOI: 10.5606/kbbihtisas.2017.46656
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Turkish version of the Eustachian Tube Dysfunction Questionnaire

Abstract: Objectives: This study aims to determine the value and discriminative power of the validated translation of the Eustachian Tube Dysfunction Questionnaire-7 (ETDQ-7) in a Turkish speaking population with and without Eustachian tube dysfunction (ETD). Materials and Methods:The ETDQ-7 was completed by 38 patients with ETD and 47 healthy individuals. The internal consistency was evaluated using the Cronbach's alpha coefficient. The receiver operating characteristic (ROC) curve was determined as an accuracy measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…14 Furthermore, a study conducted in 2015 found that the mean ETDQ-7 total score was 9.91 in a control group and 25.77 in patients with obstructive ET dysfunction, in comparison with our results, which were 17.6 and 9.87, respectively. 16 Item 3 (feeling clogged or "underwater") had the highest mean score (3.06 AE 1.78), which is consistent with another study. 17 Item 7 (feeling muffled) had the lowest mean score (1.71 AE 1.27).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…14 Furthermore, a study conducted in 2015 found that the mean ETDQ-7 total score was 9.91 in a control group and 25.77 in patients with obstructive ET dysfunction, in comparison with our results, which were 17.6 and 9.87, respectively. 16 Item 3 (feeling clogged or "underwater") had the highest mean score (3.06 AE 1.78), which is consistent with another study. 17 Item 7 (feeling muffled) had the lowest mean score (1.71 AE 1.27).…”
Section: Discussionsupporting
confidence: 90%
“…Various diagnostic tools have been suggested in an attempt to test ET function. 16 Several studies have focused on translating and testing the validity and reliability of the ETDQ-7 in regions like Europe, where various languages are spoken, including German, 15 Dutch, 16 Turkish, 17 and European Portuguese. 18 The EDTQ-7 has also been translated into Brazilian Portuguese 3 and traditional Chinese.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ETDQ-7 has been translated to nine other languages with good consistency and discriminant validity. (Table IV) [10][11][12][13][14][15][16][17][18] Our study has a comparable internal consistency reliability with other studies which reported Cronbach's alpha of 0.71-0.92. Other studies reported a cut-off point of 13.5-14.0 having excellent sensitivity of 90.7-100% and specificity of 67.0-99.9%.…”
Section: Resultssupporting
confidence: 71%
“…Studies with similar study group reported sensitivity of 87 -100% and specificity of 67 -100%. [10][11][12][13][14][15][16][17][18] Malaysia is a multicultural and multiracial country with Malay language as the common language among the population. As ETDQ-7 was originally written in English, cultural adaptation and translation of the questionnaire are required for it to be applied to our local population.…”
Section: Introductionmentioning
confidence: 99%